Flying changes - Hall, Lynn. (San Diego : Harcourt Brace Jovanovich, 1991)
Seventeen-year-old Denny and her family face hard times when her father is injured on the rodeo circuit.
Keywords: Horses -- Fiction; Country life -- Fiction